Measurement of damping capacity of pultruded glass fibre- reinforced composite by forced vibration technique - Nordin Jamaludin (1992)
The effect of strain amplitude and frequency on the loss factor of glass fibrereinforced composite (GFRC) have been investigated by forced vibrations of double cantilever rod specimens. The tests were conducted at room temperature in the frequency range of 70Hz to 320Hz and at atmospheric pressure since the effect of air damping on the rod shape specimens is likely to be small. The measured loss factor is independent of the maximum strain amplitude and increases significantly with frequency. These results indicate that pultruded GFRC has relatively high damping value